Beyond `crude pragmatism` in sports coaching: Insights from C.S. Peirce, William James and John Dewey: A Commentary - Elcombe, T. (International Journal of Sports Science & Coaching, 2017)
Crude pragmatism, despite its prevalence in practice, offers little insight or nuance to our coaching practices; and in highly charged, complex environments such as sport, such non-critical approaches to coaching are likely to cultivate little if any growth. However, to approach coaching as an artistic-scientist, rather than as an analytic-economist or ideological-cleric, alternatively demands an appreciation of malleability (growth from existing conditions), the value of communal inquiry, the ever-changing qualities of the foci of inquiry, and the recognition that multiple hypotheses may offer rich alternatives—Bertstein`s4 five features of pragmatism viewed through the prism of Darwin. Such a move away from thin consequentialism to thick pragmatism I suggest will, as Jenkins` hopes, bring philosophy alive in coaching practices. FROM AUTHOR